Expression of the neuroprotective factors BDNF, CNTF, and FGF-2 in normal and oxygen induced retinopathy - Xin, Jifu; He, Yuhong; Guo, Kai; Yang, Dayong (Frontiers in Neuroscience, 2022)
Oxygen-induced retinopathy is a type of retinal pathological neovascularization (NV) disease that leads to vision loss and translates to a significant societal cost. Anti-vascular endothelial growth factor (VEGF) and anti-inflammatory treatments have been widely used in the clinic, but the results have not been entirely satisfactory. It is necessary to explore other treatments for Ischemic retinal diseases. The oxygen-induced retinopathy (OIR) model was induced from P7 to P12 as described. Histology evaluation (HE) and retina flat mounts were checked at P17 to confirm the establishment of the OIR model. Retinal ganglion cell (RGC) degeneration was checked by transmission electron microscopy at P17 to confirm the neurological damage caused by OIR. Western blot analysis was performed at P12, P15, and P17 to study the expression of brain-derived neurotrophic factor (BDNF), ciliary neurotrophic factor (CNTF), and fibroblast growth factor 2 (FGF-2) in normal and OIR mice. Comparative analysis of the expressions of BDNF, CNTF, and FGF-2 in normal and OIR mice was performed. There were many retinal NV and nonperfusion areas in OIR P17. RGCs were degenerated at OIR P17. The expressions of BDNF, CNTF, and FGF-2 gradually increased from P12 to P17 in normal mice and were much higher in OIR mice. The expression curves of BDNF, CNTF, and FGF-2 in the OIR model were inconsistent and did not correlate with each other. This study provides evidence for changes in the expressions of BDNF, CNTF, and FGF-2 in Oxygen-induced retinopathy.